Mechanisms of Family Upbringing and its role in the Eruption of Violent Behavior Among children - bederiat, louiza; driouech, widad (Journal of Social Sciences and Humanities, 2024)
The current study aims to highlight the impact of family upbringing on children's resort to violence in dealing with difficulties; as the most effective method in such situation. This is due to the fact that the child is raised in a family of violence in all its types. Hence, the child is convinced that resorting to violence is the best way to deal with others; therefore, he/she erupts this behavior, especially outside the family. Furthermore, some families unconsciously instill some violent behaviors and attitudes in their children's minds such as encouraging their children to respond to abuse by assault and /or other misbehavior such as lying, in order to defend themselves in society. Thus, children can unconsciously acquire a violent behavior from their families that may become a feature of their personalities.